CuO nanowire/microflower/nanowire modified Cu electrode with enhanced electrochemical performance for non-enzymatic glucose sensing. (10th July 2015) - Li, Changli; Yamahara, Hiroyasu; Lee, Yaerim; Tabata, Hitoshi; Delaunay, Jean-Jacques
Abstract: CuO nanowire/microflower structure on Cu foil is synthesized by annealing a Cu(OH)2 nanowire/CuO microflower structure at 250 °C in air. The nanowire/microflower structure with its large surface area leads to an efficient catalysis and charge transfer in glucose detection, achieving a high sensitivity of 1943 μ A mM –1 cm –2, a wide linear range up to 4 mM and a low detection limit of 4 μ M for amperometric glucose sensing in alkaline solution. With a second consecutive growth of CuO nanowires on the microflowers, the sensitivity of the obtained CuO nanowire/microflower/nanowire structure further increases to 2424 μ A mM –1 cm –2, benefiting from an increased number of electrochemically active sites. The enhanced electrocatalytic performance of the CuO nanowire/microflower/nanowire electrode compared to the CuO nanowire/microflower electrode, CuO nanowire electrode and Cu x O film electrode provides evidence for the significant role of available surface area for electrocatalysis. The rational combination of CuO nanowire and microflower nanostructures into a nanowire supporting microflower branching nanowires structure makes it a promising composite nanostructure for use in CuO based electrochemical sensors with promising analytical properties.